In-vitro Nutritional Assessment of Soy Nuggets based Dog Food - Kaur, Mohneet (Indian Journal of Animal Nutrition, 2021)
The present study was conducted to evaluate the effect of different processing techniques on nutritive value and to determine appropriate inclusion level of soy nuggets (SN) in dog food. Standardized diets were subjected to different processing techniques viz. raw, boiling and extrusion. The in-vitro study was performed with two incubation stages, with gastric phase of 2 hours in the presence of pepsin, gastric lipase in HCl solution, and intestinal phase of 4 h in presence of pancreatin and bile salts in buffer solution. Data analysis revealed that extrusion improved (P<0.01) in-vitro nutrient digestibility and the best (P<0.01) response was observed in diets having 5% SN containing extruded dog food. Maximum (P<0.01) dry matter digestibility and organic matter digestibility was observed in extruded diet; No significant difference (P<0.01) was observed in crude protein digestibility at 5% SN supplementation. However, with 10% and 15% SN supplementation, no significant difference (P<0.01) was observed in raw and boiled diets, but crude protein digestibility increased (P<0.01) with extrusion as compared to raw and boiled diets. Ether extract digestibility decreased (P<0.01) in boiled diet at all the levels of SN supplementation. Irrespective of processing techniques, level of SN supplementation had shown non-significant difference in nutrient digestibility but the extent was lesser than no supplementation. Â It was concluded that SN can safely be included in dog diet at 5% level.